Answer:
At x = -2, the correct comparison for the values of both functions can be represented by :
f(x) = g(x) or f(-2) = g(-2)
Explanation:
We are given with two functions in this question, f(x) and g(x).
f(x) is given as:
f(x) = 3 - x^2
The equation of function g(x) is not given as such but their value for certain values of x are given.
What we need to compare are the values of both functions at x = -2.
g(-2) = -1 (Can be seen in the question given in the image)
f(-2) = 3 - (-2)^2
f(-2) = 3 - 4 = -1 which is equal to g(-2)